Premenstrual syndrome and quality of life of woman. Effectiveness of herbal drugs - В. Н. Прилепская; Э. Р. Довлетханова (Publishing House TRILIST, 2018)
The premenstrual syndrome (PMS) is a pathological symptom that significantly reduces the quality of a woman's life. The etiology and pathogenesis to date have not been sufficiently studied, but the diagnosis, treatment and prevention that are to be complied with have been identified. The treatment of the PMS should be differentiated, taking into account the overall and reproductive health of the woman, the concomitant diseases, the degree of severity of ICP, the portability of therapy, etc.